Determination of Artemisinin by Post-Column Derivatization High Performance Liquid Chromatography - LI, MING; WU, XIANXUE; YANG, YAN; LIN, HONG; CHAI, YUEDONG; LIN AI, HUA (Asian Journal of Chemistry, 2010)
Artemisinin (an antimalaric compound), is isolated as the active principles of the medicinal plant Artemisia annua L. A simple, rapid and high efficient method of extraction was developed. It was extracted by matrix solid phase dispersion (MSPD) and directly analyzed by post-column derivatization high performance liquid chromatography. Quantification was compared the method of MSPD with two conventional liquid solvent extraction processes of Soxhlet and super wave by F-test. The result indicated no significant difference. The production rate of artemisinin during wild plant growth (was tasted in 2 years, from Yunnan provincial yuan yan country) was determined. The recoveries range of determination is 88.1- 91.2 %. The relative standard deviation (RSD) is 4.55-6.43%. The limits of detection (LOD) are 0.1 μg/mL and the limits of quantities (LOQ) are 0.5 μg/mL.